Information and communication technologies in Germany: Is there a remaining role for sector-specific regulation? - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2004)
In order to analyze the remaining role for sector-specific regulation the focus of this paper is on those elements of the Internet periphery and Internet service provision, which are strongly based on telecommunications, in particular Internet access and Internet backbone. Section 2 deals with the role of telecommunications for the Internet, differentiating between local network access and long distance network capacity. In section 3 the new regulatory arrangements for communications services within Europe, with particular emphasis on Germany, are explained. In order to analyze the future role of sector-specific regulation from a normative point of view, in section 4 the network economic concept of a disaggregated regulatory approach is provided. Section 5 deals with phasing-out potentials for sector-specific regulation due to increasing competition within the local loop. In section 6 the role of technology-neutral regulation is considered, which implies that in an environment of competing network infrastructures sector- specific regulation should not be extended, but removed. Finally, section 7 explains the role of competition in the markets for backbone interconnectivity.
Keywords: 330; Service Provider; Telekommunikationspolitik; Netzzugang; Deutschland